2007
DOI: 10.1002/tox.20239
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nodularin in sediments, mussels, and fish from the Gulf of Gdańsk, southern Baltic Sea

Abstract: In the Gulf of Gdań sk, as in other parts of the Baltic Sea, toxic blooms of Nodularia spumigena are an annual phenomenon. In the present work, the accumulation of nodularin (NOD), a cyanobacterial pentapeptide hepatotoxin, in sediments, blue mussels, and flounders from the Gulf of Gdań sk was studied by enzyme-linked immunosorbent assay (ELISA). In the surface layers of the sediments NOD concentration ranged from 2.3 ng/g dry weight (dw) several months after cyanobacterial bloom to 75 ng/g dw during the bloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
0
41
1
2
Order By: Relevance
“…However, this study deals with the short-term effects of settling cyanobacterial blooms, and it is possible that incorporation of carbon from aged cyanobacterial matter, including N. spumigena, is higher once sediment microorganisms and meiofauna have conditioned the food source (Tenore et al 1977). Another positive effect of ageing could be toxin degradation, although Mazur-Marzec et al (2007) found high concentrations of nodularin in surface sediments several months after a bloom.…”
Section: )mentioning
confidence: 93%
“…However, this study deals with the short-term effects of settling cyanobacterial blooms, and it is possible that incorporation of carbon from aged cyanobacterial matter, including N. spumigena, is higher once sediment microorganisms and meiofauna have conditioned the food source (Tenore et al 1977). Another positive effect of ageing could be toxin degradation, although Mazur-Marzec et al (2007) found high concentrations of nodularin in surface sediments several months after a bloom.…”
Section: )mentioning
confidence: 93%
“…In fish, NOD accumulation can range from 0.1-2230 mg kg À1 dry weight, depending on the organs analysed and the technique used. In contrast, primary producers such as Cladophora fracta and Fucus vesiculosus accumulate the lowest amounts of the toxin (Sipia¨et al, 2001(Sipia¨et al, , 2002(Sipia¨et al, , 2007Karjalainen et al, 2005;Strogyloudi et al, 2006;Mazur-Marzec et al, 2007;Pflugmacher et al, 2007). Despite the low NOD concentrations reported for the lower trophic levels, it has been suggested that zooplankton may act as a toxin vector, increasing its range (Karjalainen et al, 2005).…”
Section: Nodularin Accumulation and Transfermentioning
confidence: 99%
“…E-mail: vmvascon@ fc.up.pt Tan, 2007). The cyanobacteria of brackish waters (including estuaries), however, remain under-investigated, particularly in Europe, despite a number of significant contributions (Sivonen et al, 1989;Nehring, 1993;Lehtima¨ki et al, 1994Lehtima¨ki et al, , 1997Lehtima¨ki et al, , 2000Wille´n & Mattson, 1997;Sivonen & Jones, 1999;Sipia¨et al, 2001Sipia¨et al, , 2002Sipia¨et al, , 2006Sipia¨et al, , 2007Sipia¨et al, , 2008Vasconcelos & Cerqueira, 2001;Laamanen et al, 2002;Rocha et al, 2002;Geiss et al, 2003;Hobson & Fallowfield, 2003;Lehtonen et al, 2003;Stal et al, 2003;Sobrino et al, 2004;Herfindal et al, 2005;Kankaanpa¨a¨et al, 2005;Karjalainen et al, 2005Karjalainen et al, , 2007Karlsson et al, 2005;Pere´z & Carrilo, 2005;Surakka et al, 2005;Marino et al, 2006;Mazur-Marzec et al, 2007Paoli et al, 2007;Halinen et al, 2008;Ibelings & Havens, 2008;Jo´z´wiak et al, 2008;Lopes et al, 2010;Oftedal et al, 2010;). This lack of information for brackish-water cyanobacteria is especially significant in relation to the potential for production of new bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications report production and bioaccumulation of NOD-R in invertebrates and fish in the Baltic Sea (Sipi€ a et al, 2001a(Sipi€ a et al, , 2001bKankaanp€ a€ a et al, 2005;Mazur-Marzec et al, 2007;Sipi€ a et al, 2006Sipi€ a et al, , 2007Persson et al, 2009) as well MCs in freshwater organisms (Lance et al, 2006(Lance et al, , 2007(Lance et al, , 2010Chen et al, 2005;G erard et al, 2009;Ibelings and Chorus, 2007). Except for lakes in Åland and northwest Germany (Lindholm et al, 1989;Contardo-Jara et al, 2008), hepatotoxin bioaccumulation in lakes within the Baltic Sea region has received little attention previously.…”
Section: Introductionmentioning
confidence: 98%